PERWUJUDAN NETRALITAS PEGAWAI NEGERI SIPIL DALAM KEANGGOTAAN DAN KEPENGURUSAN PARTAI POLITIK DI INDONESIA - Andika Satria Putra, Made; Budi Arsika, I Made (Kertha Negara : Journal Ilmu Hukum, 2014)
Civil servant as public authorities shall be considered as integrated part of Indonesian civil society which entails the assurance of its freedom to assembly pursuant to the stipulation of Article 28 of 1945 Constitution. One of the fundamental rights to enter into assembly is the freedom to enter into a political party, however the involvement of civil servant in political party shall serves into another debatable plane during the New Order Era where civil servant is utilized as political instrument which leads to the preference of civil servant and disrupt the productivity and service of civil servant to State. Problems raised shall be upon the existence and effort of civil servant in maintaining neutrality from the political party membership and organizational structure of Indonesia political parties. In this writing, normative legal research shall be applied in elucidating neutrality of civil servant in the board of political party by enacting Governmental Regulation No. 53 of 2010 concerning Civil Servant Disciplinary Act, Governmental Regulation No. 12 of 1999 concerning Civil Servant which Serves as Political Party Members and Governmental Regulation No. 37 of 2004 concerning the Prohibition of Civil Servant to be Political Party Member in the spirit of maintaining neutrality.
Keywords: Neutrality, Civil Servants, Political Parties